Management of Asymptomatic Perforation of a Pediatric Rectal Foreign Body into the Peritoneal Cavity Retrieved with Laparoscopy: A Case Report and Review of the Literature - Mehdi Forooghi; Hooman Kamran; Reza Shahriarirad (Case Reports in Medicine)
Rectal foreign body insertion has had an increasing trend throughout the years, whereas it is rarely reported in pediatrics. The management and treatment of these cases can become challenging, since it also can present with atypical or even no symptoms in physical evaluation. A 14-year-old boy was referred to our hospital with a history of insertion of a paintbrush into his anus four weeks before the admission. The paintbrush had perforated the colon and was in the abdominopelvic cavity; however, no symptoms of peritonitis were observed. Rectal examination, sigmoidoscopy, and colonoscopy were unremarkable. Exploratory laparoscopy was performed, and the paintbrush was taken out completely. The patient was discharged in good condition. In cases with rectal foreign body insertion, perforation without causing peritonitis or acute abdomen is possible. In these conditions, imaging examinations play an essential role in managing the patients, and laparoscopy can be a proper procedure for retrieving the foreign body.